Cytosolic localization of NADH cytochrome b5 oxidoreductase (Ncb5or). Issue 5 (26th February 2016) - Zámbó, Veronika; Tóth, Mónika; Schlachter, Krisztina; Szelényi, Péter; Sarnyai, Farkas; Lotz, Gábor; Csala, Miklós; Kereszturi, Éva
Abstract : Acyl‐CoA desaturation in the endoplasmic reticulum (ER) membrane depends on cytosolic NADH or NADPH, whereas NADPH in the ER lumen is utilized by prereceptor glucocorticoid production. It was assumed that NADH cytochrome b 5 oxidoreductase (Ncb5or) might connect Acyl‐CoA desaturation to ER luminal redox. We aimed to clarify the ambiguous compartmentalization of Ncb5or and test the possible effect of stearoyl‐CoA on microsomal NADPH level. Amino acid sequence analysis, fluorescence microscopy of GFP‐tagged protein, immunocytochemistry, and western blot analysis of subcellular fractions unequivocally demonstrated that Ncb5or, either endogenous or exogenous, is localized in the cytoplasm and not in the ER lumen in cultured cells and liver tissue. Moreover, the involvement of ER‐luminal reducing equivalents in stearoyl‐CoA desaturation was excluded. Abstract :